2020
DOI: 10.1038/s41556-020-00603-8
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in the fetal testis eliminates developmentally defective germ cell clones

Abstract: Many germ cells (GCs) are eliminated during development, long before differentiating to egg or sperm, but it is not clear why. Here, we examined how GC composition in the mouse fetal testis is altered by scheduled apoptosis during sex differentiation. Multicolored-lineage tracing revealed that apoptosis affects clonally-related GCs, suggesting that this fate decision occurs autonomously based on shared intrinsic properties. We identified extensive transcriptional heterogeneity among fetal GCs including an apop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 69 publications
(63 reference statements)
5
31
0
Order By: Relevance
“…A wave of apoptosis in the prospermatogonial population is known to occur during perinatal development and has been speculated to eliminate aberrant cells (Bejarano et al, 2018;Nguyen et al, 2019;Wang et al, 1998). Indeed, recent demonstrated that prospermatognia with developmentally defective genetic and epigenetic integrity are eliminated by apoptosis in the mouse (Nguyen et al, 2020). Based on results of the current study that showed massive apoptosis of prospermatogonia lacking RB1 activity and therefore abnormal cell cycle regulation during fetal development, we speculate that correct timing of mitotic arrest is an indicator of proper fitness that saves cells from apoptosis and disruption of this timing leads to elimination of cells that would normally contribute to the spermatogenic lineage in postnatal life.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A wave of apoptosis in the prospermatogonial population is known to occur during perinatal development and has been speculated to eliminate aberrant cells (Bejarano et al, 2018;Nguyen et al, 2019;Wang et al, 1998). Indeed, recent demonstrated that prospermatognia with developmentally defective genetic and epigenetic integrity are eliminated by apoptosis in the mouse (Nguyen et al, 2020). Based on results of the current study that showed massive apoptosis of prospermatogonia lacking RB1 activity and therefore abnormal cell cycle regulation during fetal development, we speculate that correct timing of mitotic arrest is an indicator of proper fitness that saves cells from apoptosis and disruption of this timing leads to elimination of cells that would normally contribute to the spermatogenic lineage in postnatal life.…”
Section: Discussionmentioning
confidence: 99%
“…Features of germline development are highly conserved among mammals, and stringent maintenance of genetic integrity is crucial for proper inheritance regardless of species (Barton et al, 2016;Hamer and de Rooij, 2018;Murphey et al, 2013). During germ cell development, apoptosis that occurs at both fetal and postnatal ages is believed to select for the most robust cells to persist into adulthood and generate gametes that will pass genetic information to the next generation (Bejarano et al, 2018;Nguyen et al, 2020;Wang et al, 1998). The mechanisms for biosensing of germ cell fitness are largely unknown, but apoptosis is generally required to maintain reproductive fitness through the removal of developmentally incompetent or 'undesirable' cells, thereby ultimately ensuring maintenance of gamete quality (Aitken et al, 2011;Nguyen et al, 2020;Runyan et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simultaneously deleting Bax results in bilateral tumors in all 129strain males (Nicholls et al, 2019). Deletion of Bax enables the survival of cells with a delayed or arrested development, and it increases the incidence of teratomas in mice carrying the Ter mutation (Cook et al, 2009(Cook et al, , 2011Nguyen et al, 2020).…”
Section: Programmed Cell Death Curtails Germ Cell Tumorigenesis In Mice and Humansmentioning
confidence: 99%